BLUE OCEAN STRATEGY IMPLEMENTATION AND ITS EFFECT ON ORGANIZATIONS GROWTH: A CASE STUDY OF RELIANCE JIO (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
This case study examines the implementation of Blue Ocean strategy by Reliance Jio Infocomm Limited and its remarkable impact on organizational growth in India's telecommunications industry. Using W. Chan Kim and Renée Mauborgne's Blue Ocean theoretical framework, this research analyses how Jio successfully created uncontested market space and made competition irrelevant through value innovation. The study employs secondary data research methodology, analysing financial data, market performance metrics, and industry transformation indicators from 2016-2024. Findings reveal that Jio's Blue Ocean strategy implementation resulted in exceptional organizational growth: achieving 474.61 million subscribers (40.6% market share), revenue growth from ₹40.8K crores (FY2019) to ₹1.3 trillion (FY2024), and fundamentally reshaping India's telecom landscape. The case demonstrates how strategic reconceptualization of industry boundaries can drive unprecedented organizational growth while creating new market demand. The research contributes to understanding Blue Ocean strategy application in emerging markets and provides insights for organizations seeking disruptive growth strategies.
Keywords: Blue Ocean Strategy; Organizational Growth; Telecommunications Industry; Value Innovation; Market Disruption